Analisis Pengaruh E-Recruitment dan Rekrutmen Tradisional Terhadap Kualitas Seleksi Karyawan di PT. Perkebunan Nusantara I Regional 7 Palembang Kantor Penghubung Sumatera Selatan - Made Sugi Anjeli; Sabeli Aliya; Andree Raymond (LPPM Politeknik Pratama, 2025)
Digital technology has reshaped recruitment and selection, enhancing efficiency and reach yet leaving challenges in attracting candidates who align with both technical and cultural requirements. This study examines the impact of recruitment methods on employee selection quality at PT Perkebunan Nusantara I Regional 7, South Sumatra Liaison Office. Using a quantitative associative–causal design, data from 70 respondents were collected via a Likert-scale questionnaire and analyzed with regression, t-tests, F-tests, and determination tests. Results show E-Recruitment has a positive but insignificant effect, while Traditional Recruitment exerts a positive significant effect. Together, both significantly influence selection quality, emphasizing the importance of structured hybrid strategies.